Effect of air speed on particle deposition rates in indoor building - Nurul Atikah, Azmi (2015)
Particle deposition is an important factor as it significantly influences the pollutant concentration of indoor air and thus people exposure. The goals of this study are to measure the air exchange rate at different air speed conditions studied and determine the optimum air speed condition for particle deposition rates toward better indoor air quality. The air exchange rate was measured by using a tracer gas method. The depositions of three ranges of particle sizes PM (0.3-1.0), PM (1.0-2.5) and PM (2.5-10.0) were assessed by measuring the number of indoor particle and its concentration for each of air speed conditions studied. Other than that, the environmental parameters were evaluated by using an instantaneous measurement of indoor air quality meter. In order to enhance the current understanding of the mechanism involving particle decay and deposition, measurement were made in an experimental bare room, 20.16m3 in volume with four different air speed conditions including only air conditioner on, only fan on, both air conditioner and fan on and both air conditioner and fan off. About 10cm3 of ethyl alcohol was sprayed as a particle generator for each condition studied. The finding of this study shows that air exchange rate varies from 0.89 h-1 to 2.19 h-' at different air speed conditions studied. By considering only well mixed conditions, the increased air exchange rates from 1.45 h-1 to 2.19 h-' had resulting the increased of mean particle deposition rates from 0.14 h- 1 to 0.42 h-'. Besides that, this study also shows there was little effect of mixing of the condition only fan on with air speed (0.5- 0.19) m/s which shows the lowest deposition rate at 0.14 ± 0.15 (mean ± standard deviation for all respective pairs) compared to other air speed conditions. The highest deposition rates among four conditions studied shows on the condition of both air conditioner and fan off (< 0.1 m/s) at 0.53 ± 0.2. In the context of air flow present by induced convection currents, the condition of only air conditioner on with air speed (0.1-0.14) m/s on shows greatest deposition rate at 0.42 ± 0.31, while the condition of both air conditioner and fan on with air speed (0.2-0.24) m/s shows greater deposition rate which is 0.4 ± 0.23 as compared to only fan on with air speed (0.15-0.19) mIs which shows deposition rate at 0. 14 ± 0.15. The optimum condition of air speed for particle deposition rate shows on the condition of only air conditioner on with 0.42 ± 0.31. Higher particle deposition rates also shows on PM (0.3-1.0) with 0.62 + 0.21 as compared to 0.31 ± 0.20 deposition rates for PM (1.0-2.5) and 0.20 ± 0.12 deposition rates for PM (2.5-10.0). The environmental factors such as temperature and relative humidity also affect the particle deposition rate. By not considering the conditions of both air conditioner and fan off, the increasing of temperature have decreasing the particle deposition rate from 0.42 ± 0.31 to 0.14 ± 0.15 while the increasing of relative humidity in this study have increasing the deposition rate from 0.14 ± 0.15 to 0.42 ± 0.31. As conclusions, it can be concluded that air exchange rate does not influenced by different air speed conditions and that the condition of air conditioner on is the best condition in the building.